Sports Titan / Zetty Nur Aida Ahmad Zahir - Ahmad Zahir, Zetty Nur Aida (2018)
Sports Titan, a newly innovative retail outlet and online business providing enjoyment equipment and services for all sports people. The retailer stocks a wide range of sporting goods, from tennis rackets to scuba diving equipment, usually in large superstores with good service facility to develop the best sporting store for its customers. All the energy in to developing technical, good-looking and simple products, always at affordable possible prices. These products are aimed at all sports enthusiasts, from beginners to experts and are sold exclusively at Sports Titan. Nowadays, the trend of online shopping has been increasing in numbers as the majority of people tend to have their own social media account and prefer to do online shopping instead of going to walk-in to the store. This is one of the evidence that online shopping is expected to be more develop in future, very convenient and can help the business to widen the range of getting potential customers globally.